DEVELOPMENT OF STUDENT WORKSHEETS (LKPD) BASED ON AUGMENTED REALITY TO ENHANCE CRITICAL THINKING SKILLS AND LANGUAGE PROFICIENCY IN PROSE FICTION MATERIAL - Yenny Puspita; Juaidah Agustina; Masnunah; Achmad Wahidy; Aswadi Jaya (Indonesian EFL Journal, 2026)
Innovation in learning, particularly in the development of instructional media for prose fiction, plays a critical role in enhancing the quality of the learning process. However, many educators still face challenges in utilizing technology due to limited knowledge and skills in creating digital-based learning media. This study aims to develop Student Worksheets (LKPD) integrated with augmented reality (AR) for teaching prose fiction (fantasy stories) at SMP Negeri 21 Palembang. The research adopts a development approach using the ADDIE model, which includes five stages: 1) Analyze, 2) Design, 3) Develop, 4) Implementation, and 5) Evaluation. The findings of the study highlight that the design of LKPD assisted by Augmented Reality emphasizes the use of technology in learning activities, thereby increasing student engagement and understanding of prose fiction material. The use of AR offers a more interactive and engaging learning experience, aligning with the demands of the digital era 4.0. Results from pretest and posttest assessments indicate a significant improvement in both critical thinking skills and language proficiency, particularly in the comprehension of prose fiction. In conclusion, the LKPD based on Augmented Reality is deemed feasible, practical, and effective in enhancing the critical thinking and language proficiency of grade VII students at SMP Negeri 21 Palembang in prose fiction learning. This media is recommended for further development and broader application in educational activities to support the improvement of education quality.